Seven decades of Chinese state financing in Africa: Tempering current debates. Issue 3 (2nd September 2019) - Strange, Austin
ABSTRACT: Fierce debate persists among policymakers and researchers about the nature and consequences of overseas Chinese state financing. Developing countries in Africa are a major focus of this controversy. However, popular accounts are often devoid of historical context, and instead emphasize China's emergence as a prominent aid donor since 2000. This article combines evidence on historical and contemporary Chinese development projects to revisit popular claims about the motives and effects of Chinese government financing in Africa. I delineate Chinese development finance to Africa into four periods largely based on China's own development trajectory: the early years; revolutionary diplomacy; post-reform, commercially oriented development; and the current period of global engagement. I then revisit three controversial narratives about Chinese development finance to Africa: the 'rogue donor' label; the socioeconomic and political consequences for African societies; and potential debt risks for African governments. In doing so, I also review recent evidence using the data discussed in this article. On balance, incorporating historical and recent evidence on Chinese state financing produces a mixed outlook with reasons for both optimism and concern. This contrasts with popular, highly opinionated views on Chinese financing that often extrapolate specific episodes into continent-wide narratives.